Image-guided interstitial brachytherapy boost for nasopharyngeal carcinoma: technical aspects - Murakami, Naoya; Cheng, Guanghui; Yoshimoto, Seiichi; Itami, Jun (Journal of Contemporary Brachytherapy, 2020)
Nasopharyngeal cancer generally responds well to concurrent chemoradiotherapy (CCRT). However, there is a small group of patients who respond poorly to CCRT, and experience local residual tumor or local relapse. Although several attempts have been performed to such a group of patients including re-irradiation with external beam radiation therapy (EBRT) or salvage surgery, clinical results remain unsatisfactory. Intracavitary brachytherapy (ICBT) boost after CCRT with EBRT has been explored, however, its efficacy is limited to those with superficial residual tumors. For those residual tumors thickness with more than 5 mm, interstitial brachytherapy (ISBT) boost would be an appropriate modality of choice. Here, we describe technical aspects of the high-dose-rate interstitial brachytherapy (HDR-ISBT) boost for nasopharyngeal cancer (NPC) patients who responded poorly to the CCRT with EBRT.